2014
DOI: 10.1073/pnas.1404769111
|View full text |Cite
|
Sign up to set email alerts
|

Invariant natural killer T cells act as an extravascular cytotoxic barrier for joint-invading Lyme Borrelia

Abstract: Significance Invariant natural killer T cells (iNKT) have been found primarily patrolling inside blood vessels in the liver, where they respond to bacterial glycolipids presented by CD1d on liver macrophages. We show joint iNKT cells are localized outside of blood vessels and respond directly to the joint-homing pathogen, Borrelia burgdorferi , which causes Lyme borreliosis using multichannel spinning-disk intravital microscopy. These iNKT cells interacted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 34 publications
0
81
0
Order By: Relevance
“…NKT cells specifically recognize diacylglycerol antigens from B. burgdorferi (40). They limit spirochete dissemination by killing blood-borne spirochetes in the liver (41) and act as a cytotoxic barrier to prevent spirochete entry into the joint space (42). Deletion of NKT cells resulted in more severe and prolonged arthritis and reduced ability to clear spirochetes from tissues (22).…”
Section: Discussionmentioning
confidence: 99%
“…NKT cells specifically recognize diacylglycerol antigens from B. burgdorferi (40). They limit spirochete dissemination by killing blood-borne spirochetes in the liver (41) and act as a cytotoxic barrier to prevent spirochete entry into the joint space (42). Deletion of NKT cells resulted in more severe and prolonged arthritis and reduced ability to clear spirochetes from tissues (22).…”
Section: Discussionmentioning
confidence: 99%
“…Intravital microscopy revealed that Kupffer cells take up spirochetes in the liver, and iNKT cells clustered around them (Lee et al, 2010) presumably carrying out an immune response in the liver sinusoids. These authors also showed that iNKT cell-deficient Jα18 À/À mice have a 25-fold increase in pathogen burden in the joints during this infection (Lee et al, 2010) and that iNKT cells attack the Borrelia spirochetes in the extravascular space (Lee et al, 2014).…”
Section: Borrelia Sppmentioning
confidence: 91%
“…This led to the dampening of whole body inflammation and an increased susceptibility to infection (Wong et al, 2011). Unlike the liver, iNKT cells did not patrol the blood vessels of joints (Lee et al, 2014). Instead, iNKT cells were strategically localized extravascularly along the length of the few blood vessels within the joint (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the liver, iNKT cells did not patrol the blood vessels of joints (Lee et al, 2014). Instead, iNKT cells were strategically localized extravascularly along the length of the few blood vessels within the joint (Lee et al, 2014). Upon infection with Borrelia burgdorferi, which adhered to the joint vasculature, iNKT cells were able to recognize and directly kill this pathogen and prevent infection (Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%